An Insight View on Synthetic Protocol, Surface Activity, and Biological Aspects of Novel Biocompatible Quaternary Ammonium Cationic Gemini Surfactants. Issue 1 (4th August 2020) - Akram, Mohd; Lal, Hira; Osama, Mohammad; Ansari, Farah; Anwar, Sana; Kabir‐ud‐Din,; Ahmad, Ajaz; Samreen,; Azum, Naved; Marwani, Hadi M.; Asiri, Abdullah M.
Abstract: In this study, we prepared a novel series of diester‐functionalized cationic gemini surfactants (C m ‐E2O2‐C m ) containing ethylene oxide as a spacer with varying alkyl chain lengths and characterized by 1 H NMR, FT‐IR, elemental analysis, and ESI‐MS. The physicochemical properties of the geminis were explored by tensiometry, fluorescence, dye solubilization, and Krafft point. These geminis acquire superior surface activity than the conventional surfactants. Fluorescence spectroscopy analysis affirmed that the micropolarity and aggregation number of micelles diminished with increase in the alkyl chain length. These geminis represent a new group of amphiphiles of considerably high biodegradability, better cleavability, and low toxicity as assessed by BOD test, FT‐IR analysis, and HC50 analysis, respectively. They also showed significant level of antimicrobial activity toward some specified bacterial strains of Gram‐positive and Gram‐negative by using agar well diffusion method. Furthermore, the thermogravimetric analysis provided information regarding thermal stabilities of the newly synthesized gemini surfactants. Abstract :